Media and public knowledge: news on stem-cell studies - Bertolli Filho, Claudio (FCL-UNESP Laboratório Editorial, 2007)
This text seeks to analyze the Folha de São Paulo newspaper’s focus on the employment of stem-cells in scientific research, looking into editorials, articles and reader letters published throughout 2005. The analysis of the newspaper’s own texts leaves no doubt as for the editors’ support of broad stem-cell employment in research, but the letters from readers show that not everyone agrees with the newspaper’s version of the facts. In this process, media contributes in building general public knowledge on cell and molecular biology-related themes, without, however, establishing the newspaper’s opinion as the irrefutable truth.